Level of Knowledge on Hygiene Sanitation on Food Vendors in Traditional Markets in Tarikolot Village, Sumedang - Nenden Rosana; Karpin Karpin; Yulia Rahmawati (Media Pendidikan Gizi dan Kuliner, 2021)
Knowledge of hygiene sanitation is one of the basics of a clean healthy lifestyle. The purpose of the study was to determine the implementation of a healthy market, and the level of knowledge about sanitation and hygiene among food market sellers in the traditional market of Tarikolot Village, Sumedang. The research method is using descriptive research with a quantitative approach. The population and sample of the study were the sampling technique using the census technique, namely sellers of foodstuffs such as staple foods, meat, meatballs, eggs, vegetables, and grocery with a total of 23 people. Research instruments are observation and questionnaires. The results of the level of knowledge of hygiene, sanitation for food sellers in the traditional market of Tarikolot Village are still lacking, because most of the sellers of food ingredients in the market do not know the term sanitation hygiene.